Atlas of male genitourethral surgery : the illustrated guide - Arya, M. [ (Manit)]; Jordan, Gerald H.; Muneer, Asif (Wiley-Blackwell, 2014)
Male genitourethral abnormalities are a source of great concern and distress to those affected. Surgery, when required, is very specialized and often extremely complex requiring expert surgical skills in order to achieve the best outcomes. Atlas of Male Genitourethral Surgery: The Illustrated Guideprovides urological surgeons, at all levels of experience from trainees to established specialists, with a full colour, highly illustrated and step-by-step approach to male genitourethral surgery, enabling complete mastery of surgical techniques in this difficult and challenging